2013
DOI: 10.7863/ultra.32.9.1547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Pediatric Patients With Acute Abdominal Pain and Incidental Findings of Free Intraperitoneal Fluid on Diagnostic Imaging

Abstract: We found clinical outcomes (surgical versus nonsurgical) to be most correlated with a surgical diagnosis on diagnostic imaging and not with the amount of fluid present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
(12 reference statements)
2
12
0
2
Order By: Relevance
“…The majority of patients with normal USG or findings suggestive of a non-surgical or infectious condition did not have FF while FF was common in patients with a gynecologic or urologic condition. Similarly, in the study by Matz et al, the final diagnosis was of gynecologic or urologic origin in 36% of patients who had intra-abdominal FF alone [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of patients with normal USG or findings suggestive of a non-surgical or infectious condition did not have FF while FF was common in patients with a gynecologic or urologic condition. Similarly, in the study by Matz et al, the final diagnosis was of gynecologic or urologic origin in 36% of patients who had intra-abdominal FF alone [19].…”
Section: Discussionmentioning
confidence: 98%
“…The hospitalization rate was 74.1% for patients with both FF and pathological conditions while it was 17.6% for patients with FF alone. Matz et al found a discharge rate of 48.8% for patients with FF but without a confirmed surgical pathology [19]. Also, the presence of FF alone did not affect re-admission to another health care facility (p=0.99).…”
Section: Discussionmentioning
confidence: 99%
“…In other instances, POCUS can obviate the need for further imaging such as in suspected renal and biliary colic 19,20. The use of POCUS to allow reduced utilization of computed tomography (CT) may have a significant public health benefit, with an estimated 1.5–2.0% of all cancers in the United States attributable to radiation from CT 23,24…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of pediatric patients with acute abdominal pain, free fluid on diagnostic imaging doubled the rate of a surgical condition from 25% to 57.4% (p<0.001) as well as increased the rate of surgery from 6.3% to 94.4% (p<0.001) 24. While free fluid alone is not specific for a surgical pathology, providers must consider this finding when deciding to obtain or prioritize specialty consults and more specific imaging such as CT in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Final attending radiologist readings of the MRIs and RLQ US were used. Investigators categorized RLQ US and MRI reports as 0 = demonstrating a normal appendix; 1 = not demonstrating the appendix, but not demonstrating any abnormalities consistent with appendicitis (including free‐fluid classified as either physiologic or small without other suggestive findings in adolescent girls); 2 = equivocal (more than physiologic free fluid, lymphadenopathy, inflammation of distal ileum); 3 = not demonstrating the appendix, but demonstrating evidence of appendicitis (abscess, periappendiceal inflammation); 4 = demonstrating an abnormal appendix consistent with appendicitis; or 5 = demonstrating an alternate pathology based on the radiology attending final read.…”
Section: Methodsmentioning
confidence: 99%